A comprehensive review on functionality of probiotics in edible packaging. Issue 1 (29th September 2022) - Shivani, Tholla Madana; Sathiavelu, Mythili
Abstract: Over the last few years, edible packaging has been employed in order to increase the health benefits of food and increasing its shelf‐life. Edible packaging is an alternative to typical food protection systems that is both environmentally and customer‐friendly. Concerns regarding healthy diet and well‐being have led to a worldwide surge in the usage of probiotic‐containing foods. This breakthrough has elicited the attention of scientists in the food industry, with an objective of producing novel probiotic foods and enhancing existing probiotic delivery techniques. In this context, edible packaging is being researched as a probiotic carrier with a vast array of applications. Probiotics have been added to a variety of foods and mixed into biopolymeric materials to create food packaging as a way to control foodborne pathogens, improve food safety and provide health benefits. The following review attempts to describe the edible packaging system with very current data, unexplored sources of probiotics and examines probiotics in edible packaging, its incorporation techniques and new breakthroughs in synbiotic edible packaging. Abstract : The relevance of edible packaging is growing both in terms of industrial level and consumers health aspect. It is well‐known for being environmentally friendly, prolonging shelf‐life, fighting pathogens and so on. However, incorporating probiotics into it boosts the nutritional content and provides consumer greater health benefits. In this review, we have emphasised on the effective delivery of probiotic via edible packaging, variety of application, probiotic incorporation techniques and potential of prebiotics in promoting overall viability of probiotics in edible packaging.